Rubeola Diagnostic Expert System Using Certainty Factor Method - Hasan, David Wahyu; Siswanto , Siswanto; Yupianti , Yupianti (CV. Generasi Insan Rafflesia, 2022)
So far, the puskesmas has not fully implemented information technology in it, due to the limited facilities and infrastructure used, so that all patients who wish to seek treatment must come more to get a registration number for treatment. This happens because the number of doctors at the puskesmas is not proportional to the number of patients who wish to seek treatment at the puskesmas, so that a limit is imposed on the number of patients seeking treatment every day. The application of an expert system for diagnosing rubeola disease at the Beringin Raya Nursing Health Center in Bengkulu City was created to assist the puskesmas in diagnosing rubeola disease in patients based on the symptoms experienced by the patient. In the process of diagnosis, the expert system application has applied the Certainty Factor Method which is used to obtain the percentage level of certainty for the rubeola disease. The application of an expert system for diagnosing rubeola disease at the Beringin Raya Health Center in Bengkulu City was made using the Visual Basic.Net programming language. Based on the results of the tests that have been carried out, the functional application of the expert system for diagnosing rubeola disease at the Beringin Raya Treatment Health Center in Bengkulu City is running well as expected and can provide information on the results of consultations to determine rubeola disease